2003
DOI: 10.1007/s00464-003-9002-3
|View full text |Cite
|
Sign up to set email alerts
|

Inter- and intraindividual variabilities of perforation forces of human and pig bowel tissue

Abstract: The strength of the pig bowel is approximately comparable to the strength of the human bowel, and, therefore, testing of graspers on pig bowel is justified. However, due to the large interindividual variation, large safety margins should be taken into account.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 13 publications
(12 reference statements)
0
31
2
Order By: Relevance
“…The damage-slip ratios determined on these healthy pigs can only be extrapolated to human tissue using large safety margins. Although in a previous study no differences were found between the perforation forces of healthy pig and human tissue [4], the strength of severely affected human tissue is unknown. The definition of damage used in this study was chosen so that all jaws could be compared, but the long-term effect of this kind of damage is unknown.…”
Section: Discussionmentioning
confidence: 96%
“…The damage-slip ratios determined on these healthy pigs can only be extrapolated to human tissue using large safety margins. Although in a previous study no differences were found between the perforation forces of healthy pig and human tissue [4], the strength of severely affected human tissue is unknown. The definition of damage used in this study was chosen so that all jaws could be compared, but the long-term effect of this kind of damage is unknown.…”
Section: Discussionmentioning
confidence: 96%
“…Relating the results to surgical practice, if the grasped object in this study had been human small bowel tissue, it would have frequently been perforated in condition T and GH, as pinch forces at which human small bowel is perforated are approximately 10.3 + 2.9 N (Heijnsdijk et al 2003). These perforation forces were measured with no pull force, meaning that adding a pull force would result in lower perforation forces.…”
Section: Discussionmentioning
confidence: 99%
“…In tissue manipulation, inability to control these forces is associated with slippage of the tissue if the pinching forces are too low, and with damage to delicate tissue if the forces are too high [1,6]. The surgeon usually senses the magnitudes of applied forces peripherally via mechanoreceptors in the skin and muscles [5,7].…”
mentioning
confidence: 99%